LEARNING OUTCOMES IN TRADITIONAL MEDICINE EDUCATION FROM STUDENTS’ PERSPECTIVES: A SURVEY AT CAN THO UNIVERSITY OF MEDICINE AND PHARMACY (Vietnam Journal of Community Medicine, 2026)
Objective: To assess traditional medicine students’ perceptions and ratings of the implementation of program learning outcomes at Can Tho University of Medicine and Pharmacy, to inform curricular improvement.Methods: Cross‑sectional descriptive study. A 27‑item, 5‑point Likert questionnaire was mapped to nine program learning outcomes grouped into three domains (general, foundational discipline, specialty). Data were analyzed in SPSS software with descriptive statistics, t‑tests, ANOVA, and linear regression to examine associations between demographics and program learning outcomes ratings.Results: The overall mean score across the 27 criteria was 4.29 ± 0.66; it was highest in the professional ethics domain (4.48 ± 0.76) and lowest in the first aid and emergency management domain (4.13 ± 0.83). Female students, final-year students, and those who had been introduced to the program learning outcomes tended to give higher scores; some differences were statistically significant (p < 0.05).Conclusion: Students rated the program learning outcomes system positively, with strengths noted in professional ethics, communication, counseling, and community coordination; competencies related to clinical practice/treatment remained limited. It is necessary to strengthen communication about the program learning outcomes, expand clinical practice, and integrate traditional medicine with modern medicine in training.
Keywords: Program learning outcomes, traditional medicine, student, curriculum, Can Tho University of Medicine and Pharmacy.